“The Age of Individualism” in philosophical conceptions of Sri Aurobindo - Kihno, Alexander (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2017)
The article present an analysis of historical ideas proposed by Sri Aurobindo, particularly in comparison with views of Nikolai Berdyaev. In his works a thinker proclaims the idea of principle changing of mental-historical paradigms, which, from his point of view, begins in the first half of 20th age, the end of the dominating tendency of the last centuries, tendency which coincided with the absolute prevailing of Europe on a world arena, that Aurobindo named Age of Individualism and Reason. Sri Aurobindo describes this tendency for Europe as beginning of Age of Protestantism, Age of Reason, Age of Rebelling, Progress, Freedom. Arrival of next, Subjective Age for Sri Aurobindo is unavoidable related to awakening of East for which internal subjective vision was always actual. N. Berdyaev in “Fate of Russia” also writes about awakening of asleep Asia, about prospects of this process. He also is in sort opened to the specific of east spiritual experience. But for Berdyaev Europe is not local civilization which finished the cycle of development and which only on condition of meeting with Asia can regenerate. Europe for him is foremost the Christian World, he believes in immanent possibilities of spiritual revival of Europe and Christian World. Sri Aurobindo writes about the offensive of Subjective Age, when the human soul wakes up and goes out on the first plan not only in a person but also in whole society. He describes the different signs of offensive of subjective Age – the revolutionary re-erecting in the spheres of religion, philosophy, sciences, arts and societies, the awakening of East, the new, vitalistic tendencies in literature and art.